Parent-child skin carotenoid level and vegetable intake relationships in users of children’s cafeterias in Japan - Kurotani, Kayo; Ohkawara, Kazunori; Takimoto, Hidemi (Frontiers in Nutrition, 2024)
Introduction: Studies on the relationship between parental and child dietary intakes are limited in Asian populations. Here, we examined parent-child relationships in skin carotenoid levels and vegetable intake in a Japanese community. Methods: The study participants were 58 children aged 6-15 years and 39 of their guardians (parents) using children's cafeterias. Skin carotenoid levels were measured using the Veggie Meter®, and the number of vegetable dishes (equivalent to a serving of 70 g) was evaluated using a self-administered questionnaire. Results: The mean (standard deviation; SD) skin carotenoid levels were 366.8 (74.0) in children and 315.0 (101.4) in parents. The partial correlation coefficient between parents' and children's skin carotenoid levels, adjusting for cafeteria, sex, parental dietary supplement use, and household financial status, was 0.38 (P = 0.02); after adjustment for smoking status and BMI, the positive correlation was attenuated (r = 0.25, P = 0.14). A positive correlation was observed between parents' and children's vegetable dish intake (r = 0.30, P = 0.02). Conclusion: This cross-sectional study identified a positive correlation between parent-child intake of vegetable dishes, accounting for potential confounders. However, the positive correlation observed between parent-child skin carotenoid levels may have been attenuated by internal factors such as smoking and obesity.